Specific association of IL17A genetic variants with panuveitis. Issue 4 (16th January 2015) - Mucientes, Arkaitz; Márquez, Ana; Cordero-Coma, Miguel; Martín-Villa, José Manuel; Gorroño-Echebarría, Marina Begoña; Blanco, Ricardo; Díaz Valle, David; Benítez-del-Castillo, José Manuel; del Rio, María José; Blanco, Ana; Olea, Jose Luis; Cordero, Yolanda; et al.
Abstract : Background/aims: A pathogenic role of Th17 cells in uveitis has become clear in recent years. Therefore, in the present study, we aimed to evaluate the possible influence of the IL17A locus on susceptibility to non-anterior uveitis and its main clinical subgroups. Methods: Five IL17A polymorphisms (rs4711998, rs8193036, rs3819024, rs2275913 and rs7747909), selected by tagging, were genotyped using TaqMan assays in 353 Spanish patients with non-anterior uveitis and 1851 ethnically matched controls. Results: The case/control analysis yielded a consistent association between two of the analysed genetic variants, rs8193036 and rs2275913, and the presence of panuveitis under a dominant model (pFDR =2.86E-03, OR=2.26, 95% CI 1.42 to 3.59 and pFDR =0.033, OR=1.83, 95% CI 1.13 to 2.97, respectively). Subsequently, a specific association of both polymorphisms with the diffuse form of the disease was evident in the subphenotype analysis when considering this same genetic model (panuveitis vs posterior and intermediate uveitis: rs8193036, p=0.020; rs2275913, p=0.038). Independent effects of rs8193036 and rs2275913 were observed by conditional regression analysis. Conclusions: Polymorphisms within the IL17A locus show a novel association with panuveitis. Our data agree with the elevated levels of this cytokine that are found in patients with uveitis, supporting a crucial role of Th17 cells in this pathology. Subtitle: Our results clearly evidenced the role of IL17A as a novel genetic risk factor for panuveitis, thus suggesting the implication of Th17 cells in the extensive inflammation of the uveal tract that occurs in this subtype of uveitis.